The efect of disinfectant solutions on the durability of the bond between resin based cement and non-precious metal alloy - Prema Sukumaran,; Foxton, Richard; Wilson, Ron; Mallett, Richard; Fenlon, Michael (Universiti Kebangsaan Malaysia, 2015)
This study evaluated the effect of disinfectants on the tensile bond strength of Nickel-Chromium alloy bonded with resin cement. 180 pairs of Nickel-Chromium dumbbells were prepared. The dumbbells were divided into 3 groups (n=60), which received one of the following treatments: Sandblasted only (control), sandblasted and Perform®-ID or sandblasted and sodium hypochlorite (SH) before bonding with resin cement. All bonded specimens were stored in distilled water for 24 h and half of the specimens were subsequently thermocycled (500 cycles) before debonding. Tensile bond strength was recorded and each dumbbell was examined for failure mode. Two-way ANOVA analysis indicated that overall there was a statistically significant difference between 24 h and thermocycling test, but no differences between sandblasted only, sandblasted and Perform-ID or sandblasted and SH groups. Post-ANOVA contrasts indicated that only the sandblasted and SH group showed a significant difference between the 24 h and thermocycling test. Disinfectants did not significantly decrease tensile bond strength between Nickel-Chromium dumbbells bonded with resin cement.